2008
DOI: 10.1007/s11999-008-0122-x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Elective Hip and Knee Arthroplasty by Age and Payer

Abstract: Elective joint arthroplasty improves the quality of life for patients with severe arthritis. In the United States, utilization of services varies with insurance status. We asked the following questions: (1) Is there an increase in the utilization of elective hip and knee arthroplasty after age 65? (2) Does the difference in utilization between the insured and general populations decrease at age 65 (the age at which Medicare provides near universal coverage)? (3) Does Medicare become the primary payer of electi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…Matlock et al found that prior to age 65, most TKA procedures were paid by private insurance carriers, while more than 80% of procedures for patients older than 65 were paid for by Medicare. [33] This is consistent with our finding of a significantly lower percentage of private payer status in the NIS than in the KID datasets (p < .0001). There is also a noticeable increase in procedure utilization at age 65, most likely a result of Medicare benefits going into effect for all patients over 65, including those who were previously uninsured.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Matlock et al found that prior to age 65, most TKA procedures were paid by private insurance carriers, while more than 80% of procedures for patients older than 65 were paid for by Medicare. [33] This is consistent with our finding of a significantly lower percentage of private payer status in the NIS than in the KID datasets (p < .0001). There is also a noticeable increase in procedure utilization at age 65, most likely a result of Medicare benefits going into effect for all patients over 65, including those who were previously uninsured.…”
Section: Discussionsupporting
confidence: 90%
“…There is also a noticeable increase in procedure utilization at age 65, most likely a result of Medicare benefits going into effect for all patients over 65, including those who were previously uninsured. [33,34] The analysis of the NIS database showed a correlation between private primary payer status and both length of stay and total charge (p < .0001). This relation was not seen in the KID analysis, where total charge only was correlated with length of stay in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The economic data in our study are based on charge data, which may not entirely reflect the actual costs associated with hospitalization. Some authors believe that the use of administrative claims data in orthopedic surgery outcomes research is not entirely concordant to clinical records [35, 36], but the use of administrative data allows a broad perspective on the incidence, risk factors, and implications of IF and has been used extensively by us evaluating the early outcome of TJA surgery [26, 33, 34, 37–39]. Despite these limitations, the data sample used was nationally representative of the United States and was able to provide clinically useful data for a potentially preventable complication after TJA.…”
Section: Discussionmentioning
confidence: 99%
“…This work was performed at Beth Israel Deaconess Medical Center, Harvard Medical School, Boston, MA, USA. treatment, and outcomes in orthopaedics [2,4,11,22,26], portions of the new law are of particular interest, including the requirement to maintain minimal essential insurance coverage, the creation of government-run health insurance exchanges, and the creation of new partially subsidized healthcare plans [1,21]. With millions of Americans likely to become insured, there likely will be increased demand for orthopaedic care, and it is unclear how this new demand, and incentives from novel healthcare plans, will affect practice.…”
Section: Introductionmentioning
confidence: 99%